Operation Analysis of Refrigerated Display Cabinets Based on Thermal Energy Storage and Cooling Using Natural Cold Source - Yuan Pei; He Zhengyang; Liu Aolong; Hou Feng; L; Yanli (Zhileng xuebao)
In this study, a simulation model of a natural cold source-based refrigerated display cabinet system is established by using the TRNSYS software. First, the air supply temperature of the display cabinet and the cooling temperature of the coolant are selected as variables, and the annual energy consumption is considered as the assessment index to optimize the operating conditions of the natural cold source-based refrigerated display cabinets for food storage. Second, the operating characteristics of the system are analyzed based on optimization and compared with the energy consumption of traditional food refrigerated display cabinets. The results show that the annual energy consumption of the optimal working condition system is the lowest (11 506 kW?h) when the air supply temperature of the display cabinet and the cooling temperature of the coolant is -1.5 °C is -3 °C, respectively. Compared with the traditional food refrigerated display cabinets without a natural cold source, the energy consumption of this system is reduced by 40.8%. In the optimum working conditions, the total operating time of the natural cold source-based cold thermal energy storage cooling mode and the natural cold source-based separate cooling mode is 3 739 h, accounting for 42.7% of the total running time during the entire year; the COP (coefficient of performance) of the system is 3.9, and the COP of the refrigeration unit is 4.1.